Effect of diverting stoma for rectovaginal fistula: A protocol of systematic review and meta-analysis. Issue 49 (4th December 2020) - Fu, Wenqiang; Yi, Sibin; An, Mingwei; Tang, Yong; Tang, Luwei; Wang, Yanru; Yuan, Yishun; Zhou, Qiong; Hu, Yanfang; Wen, Yiqi
Abstract: Background: Rectovaginal fistula (RVF) is a pathologic channel between the anterior wall of the rectum and the posterior wall of the vagina, is rare, and the majority is of traumatic origin. The most common causes are obstetric trauma, local infection, rectal surgery or caused by chronic inflammatory bowel disease. Once the disease will seriously affect the patient's quality of life, and generally not self-healing, most require surgical intervention. At present, diverting stoma is mainly used in patients with severe RVF or complicated RVF or patients with Crohn disease. Due to the lack of large sample, linical studies, its clinical effectiveness is still controversial. The purpose of this systematic review is to evaluate the efficacy of diverting stoma in the treatment of diverting stoma. Methods: EMBASE, PubMed, the Cochrane Library, Chinese National Knowledge Infrastructure (CNKI), Wanfang Database, Chinese Biomedical Literature Database (CBM), and Chinese VIP Information will be searched systematically by 2 reviewers from the inception until October 2020. The original study that randomized controlled trials (RCTs), clinical controlled trials (CCTs), nonrandomized control trials (NCTs), and retrospective trials (RTs) of diverting stoma for RVF will be selected. In addition, similar searches will be conducted for the reference lists, researches in progress, and the citation lists of identified publications. Study selection, data extraction, and assessment of the quality will be performed independently by 2 reviewers who have been trained prior to data extraction. A meta-analysis will be conduct if the quantity and quality of the original studies included are satisfactory; otherwise, a descriptive analysis will be conducted. Review Manager 5.4 software (The Nordic Cochrane Centre, The Cochrane Collaboration, Copenhagen, Denmark) will be using for data synthesis and assessment the risk of bias according by Cochrane Handbook. Result: This study will provide a comprehensive review of current evidence for the treatment of diverting stoma on RVF. Conclusion: The conclusion of this study will provide a judging basis that whether the treatment of RVF with diverting stoma is effective. Inplasy registration number: INPLASY2020090070.